Localization of Bovine Papillomavirus Nucleic Acid in Equine Sarcoids. (May 2016) - Gaynor, A. M.; Zhu, K. W.; Cruz, F. N. Dela; Affolter, V. K.; Pesavento, P. A.
Bovine papillomaviruses (BPV1/BPV2) have long been associated with equine sarcoids; deciphering their contribution has been difficult due to their ubiquitous presence on skin and in the environment, as well as the lack of decent techniques to interrogate their role in pathogenesis. We have developed and characterized an in situ hybridization (ISH) assay that uses a pool of probes complementary to portions of the E5, E6, and E7 genes. This assay is highly sensitive for direct visualization of viral transcript and nucleic acid in routinely processed histopathologic samples. We demonstrate here the visualization of BPV nucleic acid in 18 of 18 equine sarcoids, whereas no detectable viral DNA was present in 15 of 15 nonsarcoid controls by this technique. In nearly 90% (16/18) of the sarcoids, 50% or more of the fibroblastic cell nuclei distributed throughout the neoplasm had detectable hybridization. In the remaining 2 cases, fewer than half of the fibroblastic cells contained detectable hybridization, but viral nucleic acid was also detected in epithelial cells of the sebaceous glands, hair follicles and epidermis. A sensitive ISH assay is an indispensable addition to the molecular methods used to detect viral nucleic acid in tissue. We have used this technique to determine the specific cellular localization and distribution of BPV in a subset of equine sarcoids.